Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 7)
"Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 7)" [g0973007.jpg], n.d.